2020
DOI: 10.1371/journal.pone.0233396
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing PMTCT efforts by repeat HIV testing during antenatal and perinatal care in resource-limited settings: A longitudinal assessment of HIV seroconversion

Abstract: BackgroundMother to child transmission (MTCT) of HIV remains a challenge in resource-limited settings. Central to elimination of MTCT is effective Provider Initiated HIV Counseling and Testing (PICT). Research has shown that conducting PICT only at the initial antenatal care (ANC) visit fails to benefit pregnant women who seroconvert later in their pregnancy. This study aimed to determine the most cost effective time to perform repeat HIV testing during ANC and perinatal care (PNC). MethodsWe studied the repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…HIV testing is also the main strategy for reducing HIV-related illnesses and deaths, and new infection transmission. In addition, the success of the prevention of mother-to-child transmission (PMTCT) programme has been highlighting the role of the HIV testing service uptake in reducing HIV infection rates among children 5 6. Finally, a well-functioning HIV testing service ensures that people who are HIV negative are linked to effective prevention services 7…”
Section: Introductionmentioning
confidence: 99%
“…HIV testing is also the main strategy for reducing HIV-related illnesses and deaths, and new infection transmission. In addition, the success of the prevention of mother-to-child transmission (PMTCT) programme has been highlighting the role of the HIV testing service uptake in reducing HIV infection rates among children 5 6. Finally, a well-functioning HIV testing service ensures that people who are HIV negative are linked to effective prevention services 7…”
Section: Introductionmentioning
confidence: 99%
“…Research has emphasized the importance of conducting provider-initiated counselling and testing (PICT) not only during the initial antenatal care (ANC) visit but also at term/delivery. This is because some pregnant women may seroconvert to HIV later in their pregnancy, underscoring the necessity of repeat tests [ 41 ]. HIV incidence proportions among pregnant women who initially tested negative but later seroconverted were observed at 0.41% in Kenya [ 41 ], 0.12% in India [ 42 ], 0.5% in Zambia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya they found a seroconversion incidence of 0.41% with no speci c pattern in time during or after pregnancy when this happens. They recommended repeat testing based on risk pro le of the mother [23]. A modelling study found that a 50% reduction in transmission could be achieved with performing an HIV test at 34 weeks and 8 weeks postpartum during the rst immunization follow-up of the child [24].…”
Section: Discussionmentioning
confidence: 99%